On Auslander-Reiten components of string complexes for a certain class of symmetric special biserial algebras (2022)
Let k be an algebraically closed field. In this article, inspired by the description of indecomposable objects in the derived category of a gentle algebra obtained by V. Bekkert and H. A. Merklen, we define string complexes for a certain class C of symmetric special biserial algebras, which are indecomposable perfect complexes in the corresponding derived category. We also prove that if Λ is a k-algebra in the class C and P• is a string complex over Λ, then P• lies in the rim of its Auslander-Reiten component.